A remarkable change of the spectrum of the magnetic Of?p star HD148937 reveals evidence of an eccentric, high-mass binary - Wade, G. A. (2018)
We report newspectroscopic observations of themagnetic Of?p starHD148937 obtained since 2015 that differ qualitatively from its extensive historical record of weak, periodic spectral variations. This remarkable behaviour represents clear evidence for an unprecedented change in the character of variability of the star. In this paper, we describe the new spectral properties and compare them to the previous line profiles. Based on measurements of the radial velocities of the C III/N III emission lines near 4640 Å and the CIV absorption lines near 5800 Å, we infer that HD148937 is likely a high-mass, double-lined spectroscopic binary. Combining the spectroscopic orbit with an archival interferometric measurement of the apparent separation of the equal brightness components, we tentatively conclude that HD148937 consists of two O-type stars with masses of approximately 34 and 49 Mo, orbiting in an eccentric (e = 0.75), long-period (Porb 26 yr) orbit. We discuss the potential relationship of the binary system to the peculiar properties of HD148937, and propose future observations to refine the orbital and stellar properties.